Weight gain after castration of calves from different genetic groups - Restle, João; Muehlmann, Luiz Danilo (Semina: Ciências Agrárias, 1993)
<!--[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> The experiment evaluated the performance of beef calves, during a 17 days period, immediately after castration. Olives from six genetic groups were used, including Charolais (C), Nelore (N), 1/2 NC, 1/2 CN, 3/4 NC and 3/4 CN. From the 78 calves used, 37 were castrated. Average age of calves at castration was 243 days. Average daily gain during the 17 days period was similar (P > 0,05) for castrated and noncastrated calves. There was no interaction (P > 0,05), for weight gain, between calf treatment and genetic group.